Perennial Peanut as a Potential Living Mulch and Nitrogen Source for Citrus and Other Orchard Crops in Florida - M.A. Shahid; K. Leaks; A.R. Blount; Cheryl Mackowiak (EDIS)
The concept of using a perennial peanut as a living mulch and source of biological nitrogen in fruit and nut crop orchards is not a new idea. In Central and South America, perennial peanuts have long been incorporated as a living groundcover into palm, coffee, cacao, plantain, and citrus, as well as into other fruit and nut production orchards. This cover crop may pose as a viable, environmentally-friendly option for production in Florida, too.